PENGARUH PEMAHAMAN PERPAJAKAN, PENGETAHUAN PERPAJAKAN, TARIF PAJAK UMKM, PENERAPAN E-FILLING DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM (Studi Kasus Kecamatan Medan Marelan) - Mawaddah Mawaddah; Citra Windy Lubis (Jurnal Widya, 2024)
Taxes are official levies from the government whose collection is forced on every citizen who has fulfilled the taxpayer requirements. Taxes are used for various government purposes to improve people's welfare. This research aims to determine the influence of Understanding, Taxpayer Knowledge, UMKM Tax Rates, Implementation of E-Filling, and Taxpayer Awareness on UMKM Taxpayer Compliance. This research is quantitative research with an associative approach. The population in this study was 1,845 UMKM s in Medan Marelan District. The sampling used in this study was proportional random sampling. This research uses multiple linear regression analysis tools equipped with classical assumption tests. The partial analysis results show that Understanding, Taxpayer Knowledge, UMKM Tax Rates, Implementation of E-Filling, and Taxpayer Awareness influence UMKM Taxpayer Compliance. Simultaneous results where Understanding Tax, Taxpayer Knowledge, UMKM Tax Rates, Implementation of E-Filling, and Taxpayer Awareness influence UMKM Taxpayer Compliance